β-MnO2 nanorods investigation of dielectric properties for electronic applications - Okutan, M.; Dogan, N.; ozturk, M.; Yalcin, O. (ELSEVIER, 2021)
In this study, beta-MnO2 nanorods (NRs) were produced by hydrothermal method to describe the dielectric response of electronics and human health monitor applications. The structural properties of synthesized beta-MnO2 NRs were identified using X-ray diffraction. Frequency variation of dielectric properties for beta-MnO2 NRs was characterized by impedance spectroscopy technique. The frequency evolution of the dielectric properties for sample is associated with electrode polarization in the low frequency region. Transmission properties of beta-MnO2 NRs were attributed to Kroop's theory, Maxwell-Wagner approach, viscoelastic mechanism and Brownian motion in the high frequency regime. The complex electric modulus based on Cole-Cole plots associated with equivalent RC circuit and their adapted to the Smith-Chart diagram is investigated for beta-MnO 2 NRs in detail. Absorption coefficient (alpha) and relaxation times (tau) values for the sample were recorded 0.21 and 5.1766 x10(-5) in succession. Frequency exponent (s), which is a characteristic of conductivity, was found to be compatible with the Correlated Barrier Hoping conductivity model for beta-MnO2 NRs. (C) 2021 Published by Elsevier B.V.
Keywords: beta-MnO2 nanorods; Hydrothermal; Dielectric; Conductivity; Cole-Cole; Smith chart; HYDROTHERMAL SYNTHESIS; AC CONDUCTIVITY; IMPEDANCE; LIMN2O4; NANOCOMPOSITE; SPECTROSCOPY; ABSORPTION; CONSTANT; MODULUS; CATHODE; Chemistry